Whipple Procedure in a Patient with Duplicated Portal Vein and other Major Abnormalities in Vascular Anatomy of the Upper Abdomen – A Case Report of a Rare Finding - Parzefall, Jurgen; Girotti, Paolo; Weigl, Markus Philipp; Hanewald, Lars; Konigsrainer, Ingmar (Archives of Case Reports, 2025)
We present the case of a patient with a duplicated portal vein, a duplicated inferior vena cava, and an arterial hepatic blood supply with a single aberrant left hepatic artery. Due to carcinoma of the pancreatic head, a Whipple Procedure was performed. There were no intra- or postoperative complications, and the patient is currently in good condition with no evidence of recurrence of disease in the one-year follow-up.